2019
DOI: 10.12965/jer.1939064.352
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the recruitment of transverse abdominis through drawing-in and bracing in different core stability training positions

Abstract: There are many proposed core stability exercises in a variety of positions; however, it is not clear that in which position, activation of transverse abdominis muscle is utmost. We aimed to compare the activation of transverse abdominis muscle in different core stability exercise positions through ultrasound imaging. in a 20 subjects' study we compared the effectiveness of drawing-in and bracing maneuvers on transverse abdominis in different core stability exercise positions (supine, hook lying, supine with 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 34 publications
4
38
2
1
Order By: Relevance
“…At 10 weeks, the lumbar strengthening exercise group displayed significantly greater improvements in pain intensity, lumbar extensor strength, and psychosocial function on one of several scales. The results of previous studies indicate that sufficient exercise in low back pain patients is an effective means of decreasing pain and reducing disability [42][43][44]. Meanwhile, Rainville et al [39] suggested that exercise is safe for individuals with LBP, because exercise does not increase the risk of future back injuries or work absence.…”
Section: Discussionmentioning
confidence: 99%
“…At 10 weeks, the lumbar strengthening exercise group displayed significantly greater improvements in pain intensity, lumbar extensor strength, and psychosocial function on one of several scales. The results of previous studies indicate that sufficient exercise in low back pain patients is an effective means of decreasing pain and reducing disability [42][43][44]. Meanwhile, Rainville et al [39] suggested that exercise is safe for individuals with LBP, because exercise does not increase the risk of future back injuries or work absence.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] The thickness of transverse abdominis muscle at rest and in contraction was determined via ultrasound imaging before the intervention and at the end of five weeks of the intervention by a single sports medicine physician. 25 (Appendix B) In order to calculate the minimum sample size required in this study, the study conducted by Teresa Paolucci 12 was used. In Paolucci study, the effectiveness of Feldenkrais sports therapy showed a change in the Median (Inter-quartile range = IQR) of pain score from 2.5 (2-3) to 1 (0-2).…”
Section: Methodsmentioning
confidence: 99%
“…Upon completion of the study, the lumbar exercise group showed a significant improvement over the control group in pain intensity, as well as lumbar extensor strength. Previous studies have also indicated that sufficient exercise in LBP patients can effectively decrease pain and reduce disability [ 56 , 57 , 58 ]. Moreover, Rainville et al [ 59 ] explained that LBP patients do not have to be concerned about their safety when exercising since it does not contribute to a greater risk of injuring their backs.…”
Section: Discussionmentioning
confidence: 99%